A Library Study Of Collaborative Learning Based On Constructivism To Improve Critical Thinking Skills In Elementary School - Kurniawati, Agnes Fibriana (Multidisciplinary Journals, 2024)
This study aims to review the existing literature regarding the effectiveness of implementing constructivism-based collaborative learning in improving critical thinking skills in primary schools. The constructivism approach, which emphasizes learning as an active and interactive process, allows students to build their understanding through cooperation and discussion in groups. This learning method is expected to develop students' critical thinking skills, such as the ability to analyze, evaluate and construct logical arguments.This study uses the literature study method to collect and analyze various relevant previous studies. The results of the literature review show that constructivism-based collaborative learning can significantly improve elementary school students' critical thinking skills. Students who engage in collaborative learning show better ability in understanding concepts, solving problems, and thinking critically compared to students who learn through traditional methods. However, the implementation of this method also faces some challenges, including the need for teacher training, limited resources, and different levels of student engagement. Nonetheless, with adequate support from schools and policy makers, constructivism-based collaborative learning has great potential to be integrated in the primary school curriculum in Indonesia. This research provides practical recommendations for educators and policy makers to effectively implement constructivism-based collaborative learning. Thus, it is expected to create a learning environment that encourages the development of critical thinking skills, which are crucial for students' academic success and future life.